SMEs and knowledge-capital formation in innovation networks: A review of literature - Blandine Laperche; Zeting Liu (Journal of Innovation and Entrepreneurship, 2013)
To innovate, firms constitute a 'knowledge-capital', defined as a set of information and knowledge produced, acquired and used in the value creation process. In this paper, we focus on small and medium-sized companies (SMEs) and study their ability to develop their own knowledge-capital as well as their role in the formation of larger companies' ones. We show that while the ability of SMEs to build a strong knowledge-capital remains weak (mainly due to fewer resources), SMEs play an important role in the continuous enrichment of larger companies' ones. At the same time, their strength within larger firms' innovation networks largely depends on their ability to develop and reinforce their own knowledge-capital.
Keywords: L20; O32; O30; 650; Knowledge-capital; SMEs; Absorptive capacity; Open innovation; Networks